2019
DOI: 10.54987/bstr.v7i2.487
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Acrylamide-degrading Bacterium Isolated from Hydrocarbon Sludge

Abstract: A major source of acrylamide in soil comes from herbicide formulation that contained polyacrylamide that slowly decomposes to acrylamide. Research in acrylamide biodegradation by microbe as a tool for its bioremediation is slowly gaining attention globally. In this research, a hydrocarbon-degrading Pseudomonas sp. strain Dr Y Kertih isolated from petroleum sludge was able to grow on acrylamide. The results show that 1% (w/v) glucose supplied with acrylamide (as the only nitrogen source) was the best carbon sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 0 publications
3
45
0
Order By: Relevance
“…The results of this study show that the bacterium responsible for the degradation of acrylamide was able to make use of basic aliphatic amides, as was previously documented by other research [28,[41][42][43][44][45][46][47]. It is also unable of degrading 2chloroacetamide, an amide molecule that many degraders are unable to use.…”
Section: Discussionsupporting
confidence: 79%
“…The results of this study show that the bacterium responsible for the degradation of acrylamide was able to make use of basic aliphatic amides, as was previously documented by other research [28,[41][42][43][44][45][46][47]. It is also unable of degrading 2chloroacetamide, an amide molecule that many degraders are unable to use.…”
Section: Discussionsupporting
confidence: 79%
“…Research examining the impact of pH on acrylamide development has yielded consistent results, as seen in the present study. Many microbes that break down acrylamide prefer an environment with a pH of about 7.0 [14][15][16][17][18][19][20][21][22][23]. Soils in tropical regions often have a lower pH because of the high levels of metabolic activity that produce organic acid and carbon dioxide.…”
Section: Discussionmentioning
confidence: 99%
“…A key factor in how quickly acrylamide is broken down by bacteria is temperature. Researchers have found that several bacteria capable of digesting acrylamide thrive at temperatures close to 30 degrees Celsius [14][15][16][17][18][19][20][21][22][23]. However, thermoactive bacteria, including Pseudonocardia thermophilic and Brevibacillus borstelensis BCS-1, require higher temperatures for optimum growth, with 50(C and 55(C being required, respectively [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations